Normative nursing ethics: A literature review and tentative recommendations. (February 2020) - Vogelstein, Eric; Colbert, Alison
We describe the results and implications of a literature review that identifies the number of normative and empirical articles, respectively, that have appeared in Nursing Ethics in each year from 1994 to 2017. The results of our analysis suggest a powerful trend away from normative scholarship and toward empirical investigation within the field of nursing ethics, both overall and comparatively. We argue that there are several important negative consequences of this trend, and we propose some potential solutions to address them.